Prevalence of childhood overweight and obesity in rural Pune - Kurlekar, Utkrant; Oka, Gauri; Khare, Arundhatee (Indian Journal of Child Health, 2016)
Background: Urbanization and mechanization of lifestyle is leading to increase in childhood overweight and obesity in developing countries. Urban Indian studies report a prevalence of 5.5-24% of childhood obesity. The studies representing childhood obesity in rural areas, specifically, rural Pune are lacking. Objective: To determine the prevalence of overweight and obesity in children 10-15 years in rural Pune. Methods: Sociodemographic and anthropometric data were recorded of students from standards V to IX from a rural Pune school. Most recent and revised Indian Academy of Paediatrics (2015) body mass index criteria were applied. Results: Out of 449 children, 239 (53.2%) were boys and 210 (46.7%) were girls (mean age 12.8±1.3 years). The prevalence of overweight was 7.1% (12.5% boys and 8.5% girls) and of obesity was 3.6% (5% in boys and 1.9% in girls). Both overweight and obesity were more prevalent in boys as compared to girls. The proportion of overweight and obese children increased with higher parental educational status, being statistically significant in the case of mother’s educational status (p